MARKETABLE SURPLUS DAN FAKTOR-FAKTOR YANG MEMPENGARUHI MARKETED SUPPLY BERAS DI KABUPATEN LEBONG - Vera Octalia; Ira Primalasari (LPPM Universitas Musi Rawas, 2023)
This study aims to look at the Marketable Surplus of rice and to find out the factors that influence the marketed supply of rice marketed in Lebong Regency. The data collected are primary and secondary data. This research location was determined using the cluster sampling method with 94 respondents selected using a simple random sample. Data analysis used includes descriptive and multiple regression analysis. The results show that: 1) the marketable surplus of rice in Lebong Regency is 83.54%, the remaining 16.46%; 2) Factors influencing the marketed supply of rice marketed in Lebong Regency are: Foreign Revenue from Rice Farming and Rice Production. Keyword: marketable surplus, marketed supply, rice.